PERBEDAAN PENGGUNAAN MEDIA BERBASIS KOMPUTER TERHADAP MINAT DAN HASIL BELAJAR KIMIA DI SMAN 1 WAMENA - Ambarwati, Utami; Siregar, Tiurlina (Jurnal Ilmu Pendidikan Indonesia, 2014)
The purproses of this research are (1) to know is there any difference on student interest between class who apply media base non computer with class who did not (2) to know is there any difference studentâs result between class who apply media base on computer with class who did not (3) to know is there any Improvement on studentâs study result between class who apply media base on computer with class who did not. The population on this research is all student in class X odd semester in the year of 2012/2013 SMAN 1 Wamena with the studentâs 450. The sample that is used is studentâs in class X A as an experiment class and class X B as control class. The collection data did by using test on study result and questioner. Technique of data analysis used SPSS 16. The nominal result shows that nGain experiment 0,6 and nGain control is 0,4 the significan counting is > 0,05 and data is normal. The result of homogeneity show sig count is > 0,05 significance so both of these group have some variant or homogeny. The result of hypothesis test (test t) sig count is < 0,05 achieve Ha and reject Ho. The result of this research are (1) there is anydifference on studentâs interest between class who used media base on computer and class who did not (2) there is any significant difference on study result between who used media base on computer and class who did not (3) studentâs study result in class who used media base om computer is improve rather that class who did not. Key Word: Media base on computer, learning interest, study result, hydrocarbon